A SEM study on the use of epoxy functional vegetable oil and reactive UV-absorber as UV-protecting pretreatment for wood. (March 2015) - Olsson, S.K.; Matsunaga, H.; Kataoka, Y.; Johansson, M.; Matsumura, J.; Westin, M.; Östmark, E.
Abstract: The present study investigates the ageing performance of a UV protective system for wood, comprising the reactive UV absorber 2-hydroxy-4(2, 3-epoxypropoxy)-benzophenone (HEPBP) and epoxy functional vegetable oils (linseed and soybean oil). Scots pine samples of radial or cross-sectional surfaces were treated using a combination of the two components, or using only one of the oils. The treated samples were then aged in a Weather-Ometer for 2 × 60 h and analysed using VPSEM to follow the degradation of the wood substrate in the exact same spot before, during and after ageing. The results of the radial surfaces show slightly less degradation of samples treated with a combination of HEPBP and oil, and for the cross-sectional surfaces an even stronger protective effect is visible. For samples treated with only one of the two oils, no improvement was detectable. The radial surfaces were also analysed using FTIR where the results indicate presence of the protective treatment even after 120 h of exposure. Overall the combined pretreatment of HEPBP and epoxy functional linseed oil was concluded to have a photostabilising effect of the wood substrate.